Challenges of training for trauma recovery - Ajduković, Dean (Array, 1997)
Recovery from traumatic exposure has traditionally been considered to be a natural process, in which people were supposed to forget and put behind their suffering. In addition to the research on Holocaust survivors, Vietnam veterans and Chilean refugees during the dictatorship, which showed that traumatized people may need professional help, another cornerstone in raising the public awareness of the ways to deal with aftermath of trauma, may be the recent wars in Croatia and Bosnia and Herzegovina. These were characterized by two parallel processes: providing direct services and meeting the emerging needs of service-providers. These processes went through several mirroring phases. The first one was characterized by initial, mostly spontaneous involvement of care-providers in 1991 and early 1992. The professionals mostly used traditional skills which were readily available. The second phase saw the growth of a more professional approach and refinement of programs. The mental health professionals recognized the importance of creating supportive environment in order to support the resources of traumatized individuals. A growing number of training opportunities became available, most of which were sponsored by UNICEF which was able to bring to Croatia the leading international experts in child trauma. In the third phase, mainly during 1993, new professional issues emerged. Among these was the importance of grief process, integration of regular services and non-governmental initiatives, growing criticism of some training programs that failed to bring new competencies to the already seasoned professional providers. The fourth phase, starting in 1994, saw the already well-established centers and trauma treatment teams. Refined, comprehensive programs of psychosocial assistance to refugees were operating in Croatia. The local professionals gradually turned into trainers and were increasingly invited to present at the international forums. At the same time, the needs for more specific and sophisticated training programs became apparent. This was also the time when the Croatian non-governmental organization, Society for Psychological Assistance (SPA) became a leader in providing training in the country and Bosnia and Herzegovina. The fifth phase, starting after 1996 and the peace agreements and resettlement of refugees, opened up the needs for the social reconstruction of the devastated communities. These experiences are illustrated with examples of collaborative efforts with the international community and conceptualized as the developmental model of training for trauma recovery.